2016
DOI: 10.1111/tct.12540
|View full text |Cite
|
Sign up to set email alerts
|

Near-peer teaching programme for medical students

Abstract: These data demonstrate that NPT is valuable for both MS2s and MS4s: MS2s benefited from the social and cognitive congruence afforded by near-peer teachers, whereas MS4s used this experience to build and enhance their skills as educators. These results support the continued involvement of MS4s in this second-year course, as well as broadening the scope of and opportunities for student teaching at our medical school and beyond. Near-peer teaching is recognised as an effective method for teaching and learning wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 7 publications
2
73
0
Order By: Relevance
“…At the same time, it also provides support to the shy students who find it difficult to explain concepts or answer questions and keep order in class (Rees et al, 2016). In another study 92.3% students found it helpful to have a faculty member present during co-teaching (Gottlieb, Epstein, & Richards, 2017). Teacher supervision also seems necessary to ensure a minimum standard for the delivered content as 75% of our students required guidance to improve upon their content.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it also provides support to the shy students who find it difficult to explain concepts or answer questions and keep order in class (Rees et al, 2016). In another study 92.3% students found it helpful to have a faculty member present during co-teaching (Gottlieb, Epstein, & Richards, 2017). Teacher supervision also seems necessary to ensure a minimum standard for the delivered content as 75% of our students required guidance to improve upon their content.…”
Section: Resultsmentioning
confidence: 99%
“…Our next step was to review the educational literature for any objective, if preliminary, support for what my students had said to me in relation to NPT. Indeed, recent reviews have shown that NPT has a primarily positive impact on both learners and their teachers . But what are considered the more important mediating factors?…”
mentioning
confidence: 99%
“…Although students found the teaching to be an enjoyable experience, time management was difficult. The second years reported that the quality of the teaching was similar to or better than being taught by a faculty member alone . This Harvard study focused on respiratory pathophysiology, whereas a UK paper reports on peer tutors teaching ultrasonography to more junior medical students.…”
mentioning
confidence: 99%